Proyecto de desarrollo de un plan de marketing estratégico para la introducción de nuevas marcas de la fundación acción solidaria en el mercado de Guayaquil. - Plaza Guerrero, Leonardo Andrés (2009)
The hope of using the talents that have been acquired for something else than our own good was the main motivation for this project, which is looking for help a foundation with its projects. Keeping aside the traditions of a regular foundation, which asks for help basing on their names and for their project, "Accion Solidaria" offers products with a high quality in order to get revenues. These profits needed to increase in order to support these projects .With this requirement said, we came up with the idea of creating the best product that FAS has had so far; Vienna yogurt. Both financial and marketing strategies were made in order to get a stronger impact in our target group which includes individual from 20 to 45 years old. Our principal aim was to get a percent of the market, which lets us to grow up as a brand in the long term, by using the image of the foundation. Furthermore, it will help us to launch the rest of line of products in the future. Moreover, the main message that we want to transmit is that Vienna yogurt is a healthy product due to its handicraft elaboration which generates not only jobs for the Ecuadorian families, but also opportunities for the children to have a better standard of living in the future.